Fenomena Tradisi Pantangan Pernikahan Ngalor-Ngetan - Emi Rahmawati; Fafi Masiroh (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2020)
Marriage is a bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on the Godhead. Marriage is generally often associated with culture, especially in Indonesia which is rich in culture. The culture is able to give birth to a tradition, so many people who consider the tradition must be done. One tradition in marriage is the tradition of marriage abstinence from Ngalor-Ngetan which is found in the Village of Cekel, Karangrayung District, Grobogan Regency. The tradition is part of the tradition in the village of Cekel that has been passed down for generations and is applied to the community who will hold a wedding. As the development of Islam and knowledge in the era of globalization, some people in the village of Cekel still considered the marriage restrictions on Ngalor-Ngetan would cause disaster if the prospective bride and groom implement the restrictions. This study discusses the history and implementation implementation of Ngalor-Ngetan marriage restrictions Ngalor-Ngetan through descriptive analysis based on data that has been obtained from interviews, observations and documentation. The results of this study, abstinence from Ngalor-Ngetan marriage are still held firmly by almost all people in the village of Cekel. However, there are some people who do not believe in the tradition of abstinence from marriage because it is considered only as a suggestion and not in accordance with the teachings of the religion they believe. Besides that, some of the young people also did not pay much attention to this Ngalor-Ngetan custom. They adhere to this custom solely because they respect the demands of parents. But some others still hold fast and abide by this custom.